Incentive-Based Performance Evaluation Model for Healthcare Professionals in Hospitals: a Systematic Literature Review - Ni Luh Putu Sri Widani; Qurrotul Aini (Jurnal Infokes, 2026)
Background: Health workers are the spearhead of hospitals whose performance is significantly influenced by reward systems, yet current incentive implementations often lack transparency and holism. This study aims to identify and classify various performance appraisal models based on service incentives through a systematic literature review approach. Method: The research method utilizes a systematic review design following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A structured literature search was conducted on Scopus, PubMed, ScienceDirect, and Google Scholar databases with inclusion criteria for empirical articles published between 2021–2025. Results: The synthesis results of 10 selected studies indicate that performance-based incentives significantly increase productivity, motivation, and multidisciplinary team collaboration in hospitals. Factors such as psychological well-being, managerial transparency, and altruism values were found to be important moderators influencing the effectiveness of financial incentives. Furthermore, the use of information technology and clinical quality indicators is proven to strengthen the objectivity of medical staff performance evaluation systems. Conclusion: This study concludes that a fair and managerially integrated incentive-based performance appraisal model is a crucial instrument in improving sustainable healthcare quality